Recreational sports event participants' attitudes and satisfaction: cross-cultural comparisons between runners in Japan and the USA. Issue 3 (3rd May 2016) - Okayasu, Isao; Nogawa, Haruo; Casper, Jonathan M.; Morais, Duarte B.
Abstract : Over the past two decades, sports tourism has become significantly popular worldwide. Marathons, an especially popular type of athletic event, have both influenced and been influenced by tourist activity. In this regard, profitable and sustainable marathons may necessitate that event planning practitioners understand event participants' attitudes and needs, contributing to repeat attendance. Furthermore, cross-cultural research may help marathon organizers understand how cultural and other similarities and differences might relate to increased fulfilment of participants' needs and wants. The purpose of this study is to make a preliminary assessment of the expected relationship between event participation and loyalty in a marathon event in two countries. A total of 420 participants, of whom 200 participants were from the United States of America's event and 220 participants from the Japan event, were included in this study. In the result, marathon participants' attitudes towards and loyalty concerning the events indicated no significant differences stemming from gender, age, or full-versus-half marathon participation.